Evaluation of the effect of the chitosan/carrageenan ratio on lovastatin release from chitosan/carrageenan based biomaterials. (27th October 2022) - Hung, Ha Manh; Manh, Vu Quoc; Thao, Vu Thi Thu; Thuy, Dao Thi Phuong; Dung, Pham Tien; Viet, Nguyen Thi Bich; Linh, Duong Khanh; Linh, Nguyen Ngoc; Oanh, Doan Thi Yen; Chinh, Nguyen Thuy; Hoang, Thai; Trung, Vu Quoc
Abstract: The chitosan/carrageenan/lovastatin biomaterials were prepared using a solution technique with 5 % lovastatin and a variable chitosan/carrageenan mass ratio. Fourier transform infrared spectroscopy (FT‐IR) and field emission scanning electron microscopy (FESEM) images revealed that the complex's components were well dispersed into each other without changing the chemical structure, forming dipole interactions and hydrogen bonds among them. The abilities to release Lovastatin (Lov) in pH 2 and pH 7.4 solutions, corresponding to the environments in stomach and intestinal fluids, respectively, are both affected by the ratio of polymer components. The best results were obtained with the chitosan/carrageenan/lovastatin (w/w/%w = 10/90/5%) (CsCL195) biomaterial sample in which the particles are evenly dispersed. While the drug release process was poor in the pH 2 solution (gastric juice), a good release observed in the pH 7.4 solution (intestinal fluid) allows facilitating drug absorption through the intestinal mucosa cells into the blood, from which the effects of hypercholesterolemia treatment can be obtained. Abstract :